Al-‘Ashālāh wa al-Mu’āshirah fī al-Dirāsāt al-‘Islāmīyya - Tulus Mustofa (Al-Jami'ah: Journal of Islamic Studies, 1998)
Muslims today are suffered from rational crisis that may lead to the crises of muslim world in many aspects of life.  In order to protect and encourage their potentials and dynamism, the muslims have to get out of the   illness.  One of the ways to save them is by rethinking the methods of studying   Islam.  This particularly after the decline of muslims in almost all muslim countries as a result of the rise of Western thinking methods introduced by orientalists. Students who devoted themselves in Islamic studies find that there are two contradictive ways of approaching Islam; traditional and modern.  The traditionalists try to keep the existing approaches, while the reformists call for reform and even "westernization” In this field, there are books that have been written by scholars to synthesize them. In this paper, the writer tries to describe some of them analyzing their contents under the topic Traditionalism and Modernism in Islamic Studies.’’ The paper summarizes:The study of Islam carried out by muslim scholars has a close relation to religious mission, therefore they may not be separated theoretically as well as practically and must be separated from methods come from outside Islam.The   methods   of studying Islam in Islamic universities ought to combine   the traditional and modern ones.Some   elements of traditionalism are; the necessity of the knowledge of Islamic   civilization.  being proud of Islam, keeping the principles of Islam as well as the teaching of "salaf”’, then keeping the inherited tradition.The elements of modernism are; the importance of understanding the time, science. technology, future thinking and keeping human rights.This field of study is very broad and this paper is only a small part of it, so it needs suggestion from scholars especially experts of this field.[Mayoritas umat Islam saat   ini sedang     dilanda krisis pemikiran yang pada akhirnya membawa dunia islam kepada krisis diberbagai bidang. untuk dapat meningkatkan potensi dan dinamisme yang dimikiki umat Islam harus keluar dari situasi yang tidak menguntungkan ini. Di antara jalan keluar dari krisis ini adalah dengan memperbaiki metode studi Islam, khususnya setelah terjadinya kemunduran di bidang ini sebagai akibat dari munculnya pengaruh-pengaruh asing yang dibawah oleh para orientalis. Para   pelajar dan mahasiswa merasakan adanya dua arus yang saling bertentangan, yaitu antara   kaum tradisionalis yang mendukung tetap dijaganya metode kajian Islam yang telah ada dengan kaum reformis yang menyeruhkan   perubahan dan "westerisasi” yang pada akhirnya menimbulkan kebingungan pada mereka.  Untuk menengahi persoalan ini banyak buku-buku yang telah   ditulis oleh para   ahli sebagai upaya memadukan kedua kutub tersebut. Dalam makalah ini penulis mencoba memunculkan beberapa buku mengenai bahasan ini dengan memberikan beberapa analisis yang terangkum dalam judul; "Tradisionalisme dan Modernisme dalam Studi Islam".  Di sini penulis memberikan beberapa kesimpulan:Ada benang merah yang   menghubungkan studi Islam yang dilakukan sekarang ini dengan misi   kenabian, oleh sebab   itu keduanya tidak boleh dipisabkan, baik   teori maupun praktek sebagaimana pula harus dipisahkan dari metode yang datang dari luar.Studi Islam di Perguruan Tinggi harus menggabungkan kedua metode; tradisional dan modem.Di   antara unsur-unsur tradisionalisme adalah; keharusan mengetahui peradaban Islam, bangga   dengan baju Islam, kembali kepada pokok ajaran Islam, menghidupkan  ajaran salaf serta  melestarikan tradisi. Adapun di antara unsur-unsur moderisme adalah;  keharusan mengetahui  kondisi  zaman,  mengetahui     ilmu pengetahuan, teknologi,  berpandangan futuristik serta  menjaga hak-hak asasi  manusia.Pada dasarya   kajian  ini sangatlah luas sementara tulisan  ini  masih sangat dangkal,  oleh sebab  itu kritikan serta  perbaikan  untuk pengembangan sangat diharapkan]